Electrorheological polishing performance of cerium-doped titanium dioxide particles - Hu, Xufeng; Sun, Han; Yang, Zhiyao; Zhao, Xiaopeng; Yin, Jianbo (Frontiers in Materials, 2022)
Electrorheological (ER) polishing as a new type of polishing technique has flexibility and controllability. However, ER polishing cannot be widely used in actual processing because the present ER polishing fluid is usually prepared by simple mixing abrasive materials into ER fluid, which is easy to occur phase separation and decreased ER performance. This paper develops a new type of ER polishing material based on cerium-doped titanium dioxide. As a classic abrasive, the cerium oxide not only has high polishing performance but also can enhance ER performance of titanium dioxide by doping effect, which endows the cerium-doped titanium dioxide with high ER polishing efficiency compared to ER polishing fluid prepared by a simple mixing method. Cerium-doped titanium dioxide particles were prepared by the sol-gel method. The size, surface morphology and elemental distribution were characterized. The ER properties were tested. The effects of different concentrations, machining gap, voltage and rotation speed on polishing performance were studied. Under the conditions of a 0.2 mm machining gap, 3 kV voltage and 200 r/min rotation speed, the surface roughness (Ra) of the copper workpiece decrease from 136 nm to 14.4 nm after 0.5 h of polishing, which is far higher than the polishing efficiency of simple mixed ER polishing fluid.